Efektivitas Pembelajaran Daring Di Masa Pandemi Covid-19 Pada Jenjang Sekolah Dasar Di Daerah Bendungan Kecamatan Cimanggung Kabupaten Sumedang - Naila Lutfi Fadilah (Jurnal Pengabdian Masyarakat PGSD, 2022)
The Bendungan area is one of the areas in Cimanggung District, Sumedang Regency. The rapid spread of Covid-19 and its impact on various sectors was also felt by the Bendungan community. This Community Service is motivated by the existence of fully online learning as a result of Covid-19 when there are rumors that online learning is less effective because there has been no maximum preparation from field implementers, parents, and students, as well as in terms of regulations and facilities. online learning infrastructure. Therefore, the author has the desire to conduct an initial study as the basis for an action program to increase the level of effectiveness of learning, because there should be no missing learning content during this pandemic. The purpose of this program is to find out the effectiveness of online learning during the Covid-19 pandemic at the elementary school level in the Bendungan area, Cimanggung District, Sumedang Regency. The program method used is a review of learning assistance method through a survey. The instrument used, namely the Google form questionnaire which was distributed online via the WhatsApp Group. In this study, there were 30 grade 3 students. Based on the results of the program, namely the lack of effectiveness of online learning due to obstacles One of the obstacles that make online learning less effective is the student economy, internet connection, and teacher-student interaction. So the preparation of the assistance program needed by students is in the form of a facility and psychological assistance program. Facility assistance programs can be carried out by related agencies and authorities but also by non-governmental organizations. Meanwhile, psychological strengthening assistance for students must involve parents. The results of this survey program are expected to become the basis for policymakers to resolve similar problems